2015
DOI: 10.1007/s10660-015-9204-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile commerce and device specific perceived risk

Abstract: This study examines the role of perceived risk and access device type on consumers' on-line purchase decisions. We use a two-step hurdle approach to estimate consumer behavior. In the first step, the decision of whether to engage in eCommerce is estimated and in the second step, how many orders to place is estimated. We use a large multi-year survey sample of households from Canada's national statistical agency-Statistics Canada. The sample size is such that we are able to conduct sub-sample analysis of PC-onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…According to a recent study on device type (Zhou et al, 2020), consumers on a PC tend to write product reviews more positively than those on a smartphone, suggesting that the effects are more aligned with the screen size effects than the input mode effects, at least in regard to emotional responses. However, as shown in Appendix A, it still remains unclear whether users have similar responses, and none of the existing studies on device type (Cozzarin & Dimitrov, 2016; Kaatz et al, 2019; Seeger et al, 2019; Wang et al, 2015; Zhou et al, 2020) have tested whether and how device types (whereby both screen size and input mode vary) affect the accuracy of product size estimations. In the next section, we discuss related research including the device studies and hypothesize the potential effects of device type on product size estimations.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…According to a recent study on device type (Zhou et al, 2020), consumers on a PC tend to write product reviews more positively than those on a smartphone, suggesting that the effects are more aligned with the screen size effects than the input mode effects, at least in regard to emotional responses. However, as shown in Appendix A, it still remains unclear whether users have similar responses, and none of the existing studies on device type (Cozzarin & Dimitrov, 2016; Kaatz et al, 2019; Seeger et al, 2019; Wang et al, 2015; Zhou et al, 2020) have tested whether and how device types (whereby both screen size and input mode vary) affect the accuracy of product size estimations. In the next section, we discuss related research including the device studies and hypothesize the potential effects of device type on product size estimations.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Performance risk is divided into economic, temporal, and effort, while psychosocial risk is classified into psychological and social risks (see Table 1). There are various studies on risk perception in the existing e-commerce literature, and it was found that several types of risks affect customer beliefs and attitudes toward e-commerce services [11,18,24]. In our study, we conducted a preliminary interview with customers.…”
Section: Facets Of Perceived Riskmentioning
confidence: 99%
“…Wang et al (2015) addressed key factors in and consequences of customers’ adoption of mobile shopping such as habitual purchase, customer characteristics, order characteristics, and customer spending before mobile shopping. Cozzarin and Dimitrov (2016) identified that online security and price greatly affect m-commerce use and that the impact of perceived risk on purchase decision is greater for m-commerce than PC-based commerce shoppers. Köster et al (2016) argued that the interaction of online vendors and mobile payment providers affects customers’ risk perception and transaction intention in the context of m-commerce.…”
Section: Literature Reviewmentioning
confidence: 99%